Methods article for a study protocol: study design and baseline characteristics for aldosterone synthase inhibition in chronic kidney disease - Tuttle, Katherine R.; Rossing, Peter; Hauske, Sibylle J.; Cronin, Lisa; Hussain, Joanna; de Zeeuw, Dick; Heerspink, Hiddo J.L. (American journal of nephrology, 2023)
Introduction: Aldosterone synthase (AS) inhibition may overcome increased aldosterone production in response to renin-angiotensin system inhibition. BI 690517 is an AS inhibitor under investigation for chronic kidney disease (CKD). Methods: This multinational, phase II, double-blind study (NCT05182840) investigated the efficacy and safety of daily oral BI 690517, with or without empagliflozin 10 mg, in participants with CKD. The primary endpoint was change from baseline in urine albumin:creatinine ratio (UACR) at week 14. Between February 18, 2022, and December 30, 2022, 714 adults already treated by angiotensin-converting enzyme inhibitor (30.5%) or angiotensin receptor blocker (69.8%) were randomized (1:1) to an 8-week run-in to assign background empagliflozin (n = 356) or placebo (n = 358). Participants in each group were then randomized (1:1:1:1) to a 14-week treatment period with BI 690517 (3 mg, 10 mg, or 20 mg) or placebo. Of the 714 participants who entered run-in, 586 were randomized to the treatment period. They were predominantly men (66.6%) of white race (58.4%) with a mean (standard deviation [SD]) age of 63.8 (11.3) years. Type 2 diabetes was present in 414 participants (70.6%). The baseline mean (SD) estimated glomerular filtration rate was 51.9 (17.7) mL/min/1.73 m2, and median (interquartile range) UACR was 426.3 mg/g (205.3-888.5). Conclusion: This study will inform dose selection for further clinical development and determine whether BI 690517, with or without background empagliflozin, has a favorable safety profile and potential for additive kidney protection in participants with CKD already treated with a renin-angiotensin system inhibitor.